Innovative Preservation Technology for the Fresh Fruit and Vegetables - Pace, Bernardo; Cefola, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The preservation of freshness of fruits and vegetables until their consumption is the aim of many research activities. The quality losses of fresh fruit and vegetables during cold chain are frequently attributable to an inappropriate use of postharvest technologies. Moreover, especially when fresh produce is transported to distant markets, it is necessary to adopt proper storage solutions in order to preserve the initial quality.Nowadays, for each step of the supply chain (packing house, cold storage rooms, precooling center, refrigerate transport, and distribution), innovative preservation technologies are available that, alone or in combination, could preserve the fresh products in order to maintain the principal quality and nutritional characteristics. In this Special Issue, these preservation technologies will be described, highlighting their effect on quality maintenance.